Soret Effect and Chemical Process on MHD Oscillatory Flow in a Physiological Fluid - R. Kavitha; Nyagong Santino David Ladu; S. Ravi (Applied Bionics and Biomechanics)
This paper investigates the impact of chemical and Soret reactions on magnetohydrodynamic (MHD) oscillatory flow in a porous arteriole. Using appropriate mathematical techniques, a model of a mathematical equation is developed and solved. The flow governing equations are formulated based on certain assumptions. Exact solutions are attained for the profiles of velocity, temperature, and concentration. To highlight the key features, the numerical computations of the physical parameters, Grashof number, Reynolds number, Magnetic number, and Soret number were presented graphically. The present study reveals the viscoelasticity of blood significantly reduces flow velocity. And also illustrates blood flow (BF) in the artery is affected by the Lorentz force, which causes the velocity of the BF to increase as the magnetic field parameter values increase. The obtained outcome may be very useful in controlling BF during the surgical procedure.